Acquired Lymphangioma Circumscriptum of the Penis Treated by Electrocoagulation - Julie Bonini; Océane Ducharme; Berengere Ponroy; Jean-Noel Dauendorffer; Emilie Baubion (Karger Publishers, 2019)
Lymphangioma circumscriptum (LC) is a vascular malformation resulting from a developmental anomaly of the superficial lymphatic system of the skin. It is benign albeit uncommon. LC less frequently occurs on the penis. LC may be either congenital or acquired. Acquired cases appear to develop most frequently after interventions in the area or underlying pathologies. It is often mistaken for genital warts or molluscum contagiosum. We report here about a case of LC misdiagnosed with genital warts for 15 years. A biopsy eventually provided histopathological evidence. Various treatments are available for LC including surgical excision (which is the gold standard), CO2 laser ablation, cryotherapy, flash lamp pulsed dye laser, and electrocoagulation therapy. For our patient, one session of electrocoagulation was performed under local anesthesia. This treatment allowed an almost complete regression of the lesion without recurrence after 3 years of follow-up. Electrocoagulation may be an efficient treatment for LC in locations that may be surgically challenging such as penis.